The Best American Short Stories, 1952 : selected from U.S. and Canadian magazines - Tan, Amy.; Kenison, Katrina (Boston : Houghton Mifflin, 1952)
The Best American series is the premier annual showcase for the country's finest short fiction and nonfiction. Each volume's series editor selects notable works from hundreds of periodicals. A special guest editor, a leading writer in the field, then chooses the best twenty or so pieces to publish. This unique system has made the Best American series the most respected, and most popular, of its kind.
Foreword -- Introduction / Amy Tan -- The hermit's story / Rick Bass -- The sun, the moon, the stars / t
Keywords: Short stories, American; American fiction -- 20th century; Short stories, Canadian; Canadian fiction -- 20th century